A mesoscale fatigue progressive damage model for 3D woven composites. (November 2021) - Guo, Junhua; Wen, Weidong; Zhang, Hongjian; Cui, Haitao
Highlights: A fatigue progressive damage model for 3D woven composites (3DWC) is proposed. Damage irreversibility and crack closure effects are considered in the model. The predicted fatigue lives of 3DWC are all within two-fold error band. The proposed model can effectively evaluate the fatigue damage process of 3DWC. The predicted fatigue life rises with the cyclic jump and stress ratio increase. Abstract: A mesoscale fatigue progressive damage model (FPDM) is proposed for fatigue life prediction and failure behavior assessment of 3D woven composites (3DWC). The Hashin's fatigue criteria and the maximum tensile/shear stress criteria are used as damage activation criteria for the yarn and resin-rich matrix, respectively. A fatigue damage evolution model is developed based on Fang's static-load damage evolution model, where the damage irreversibility and compressive crack closure effect are considered. The UserMat subroutine and APDL language in ANSYS are employed to implement the fatigue process of 3DWC. The results show that all predicted fatigue lives are within two-fold error band.